RESEARCH ON PLATING PARTS USED IN THE OIL INDUSTRY - Radu Gabriel ALBULESCU; Dan DOBROTĂ; Marius Cornel TEODORESCU; Adrian Ioan DRAGOMIR (Fiabilitate şi Durabilitate)
The paper includes a number of theoretical and experimental results on plating of several pieces from different classes focusing especially on the pieces of the flanges and housings class. For reasons of confidentiality to beneficiaries, the paper presents experimeindustry at the ends of probe drilling and extraction. Have been taken into account these kinds of pieces in the research due to operating conditions and high requests which occur during operation.